Exploring the Impact of Smart Healthcare Technology on Medical Cost Control in China’s Aging Society and Its Strategic Approaches - Lin Xinying (SHS Web of Conferences)
China is facing a severe aging population challenge, with the continuous growth of the elderly population imposing significant pressure on the healthcare system. Smart healthcare, as a novel model of delivering medical and health services through modern information technologies, demonstrates immense potential in controlling medical costs and enhancing the quality of healthcare services. This study analyzes the application of smart healthcare technology in medical services for China’s aging society and examines its impact on medical cost control. Based on these findings, the paper proposes strategies to address the associated challenges. The rising demand for healthcare services driven by the growing elderly population has created a substantial economic burden in China’s aging society. Traditional healthcare models, which are both time-consuming and costly in managing a large number of geriatric patients, face enormous pressure in cost control. The introduction of smart healthcare technologies offers a promising solution to this dilemma. Through telemedicine services, electronic health records, intelligent monitoring devices, and data analytics, smart healthcare technologies not only improve the timeliness and accuracy of medical services and reduce unnecessary outpatient visits and hospitalizations but also enable long-term health management for patients. This approach effectively mitigates the burden on healthcare institutions while enabling the optimal allocation and utilization of medical resources.